Students’ use of Cloud Storage in their Studies: A Case of a Private University in the Philippines - Tubay, Jerwin Baquir (Journal of Education and e-Learning Research, 2020)
This paper seeks to determine factors affecting the students’ intention to use and actual use of the cloud storage systems such as Google Drive, iCloud and Microsoft One, etc. using the Unified Theory of Acceptance and Use of Technology. The respondents are students of leading private universities in the Philippines and the data were analyzed using Partial Lease Square – Structural Equation Model (PLS-SEM). PLS-SEM was conducted using SMART PLS software and the results showed that performance expectancy and social influence positively and significantly affects the intention to use cloud storage systems. Hence, the University should maintain its subscription of a cloud storage system and promote maximizing its use because large members of the academic community, the students, intend to use the cloud storage system as they perceive an increase in productivity of their schoolwork and due to increase by the community as well.